Erratum to: Barriers and facilitators to the implementation of orthodontic mini implants in clinical practice: a systematic review. - Meursinge Reynders, R; Ronchi, L; Ladu, L; Di Girolamo, N; de Lange, J; Roberts, N; Mickan, S (BioMed Central, 2016)
Erratum: After publication of the original article [1], the authors noticed that one of their correction requests had been missed: In Table 8, column "Prevalence of the barrier", a superscripted "a" was included next to the "5 %" and "1 %" prevalence data. These "a"s should have been removed. This is now corrected in the original article and also shown in the below table. We apologise for any inconvenience caused by this error.